Transgender history : the roots of today's revolution - Stryker, Susan (Seal Press, 2017)
"A timely second edition of the classic text on transgender history, with a new introduction and updated material throughout. Covering American transgender history from the mid-twentieth century to today, Transgender History takes a chronological approach to the subject of transgender history, with each chapter covering major movements, writings, and events. Chapters cover the transsexual and transvestite communities in the years following World War II; trans radicalism and social change, which spanned from 1966 with the publication of The Transsexual Phenomenon, and lasted through the early 1970s; the mid-'70s to 1990-the era of identity politics and the changes witnessed in trans circles through these years; and the gender issues witnessed through the '90s and '00s. Transgender History includes informative sidebars highlighting quotes from major texts and speeches in transgender history and brief biographies of key players, plus excerpts from transgender memoirs and discussion of treatments of transgenderism in popular culture."--